Field study on thermal comfort in Malaysia - Hussein I.; Rahman M.H.A. (EuroJournals, Inc., 2023)
A field study on the environmental conditions and occupant comfort was carried out in two schools, which is a primary and secondary school, and in a public waiting area in a health clinic in Johor Bahru, located in the southern region of Malaysia. These buildings were mechanically ventilated by fans. The study was made in three different days from morning until noon as to get variation of temperatures, collecting a full set of objective physical measurements and subjective assessments through questionnaires. The measured environmental parameters were air temperature, relative humidity and air velocity. The subjective responses concern the judgment of the respondents about the thermal environment at the moment of measurements. The results obtained showed that more than 80% of the respondents found that their indoor thermal conditions acceptable even though the thermal sensation votes (TSV) exceeded those specified by ASHRAE Standard 55 and the environmental assessments exceeded the standard. The neutral temperature and comfort range were obtained through linear regression analysis of TSV and in the Fanger's PMV model. From the subjective assessment, it was found that the occupants can accept the thermal range beyond the ASHRAE comfort zone. In this study, it seems that the occupants in the tropic environment such as Malaysia have a higher heat tolerance and can adapt to the environment that they are used to. EuroJournals Publishing Inc. 2009.